Snowball Throwing Learning Model Assisted by Balinese Songs and Its Impact on Students’ Cultural Literacy - Pratama, I Kadek Wahyu; Antara, Putu Aditya; Yudiana, Kadek (Jurnal Pendidikan Multikultural Indonesia, 2023)
Cultural literacy is an individual's ability to understand and behave towards a nation's culture as part of national identity. This research aims to analyze the impact of the Snowball Throwing learning model assisted by Balinese songs on the cultural literacy of elementary school students. The type of research is a quasi-experiment with a non-equivalent control group design. The research population was 162 grade V students. Samples were taken using the Random Sampling technique with an intact group. The data collection method uses multiple-choice objective tests. Research data were analyzed using descriptive statistical techniques and inferential statistics (t-test). The results of the data analysis showed that the average pre-test score for the experimental group was 13.57 in the low category, and the average pre-test score for the control group was 13.93, which was in the low category. The post-test average of the experimental group was 20.038, which was in the medium category, while the post-test average of the control group was 16.103, which was in the low category. The results of the t-test analysis showed that the t-count (3.448) was greater than the t-table (2.005), so H0 was rejected, and H1 was accepted. Thus, there is a significant influence between the group taught using the Snowball Throwing model assisted by Balinese songs and the group not taught using the Snowball Throwing model assisted by Balinese regional songs in elementary school students